(untitled) (Revista INTEREDU11, 2024)
The study presents an intervention conducted in a subsidized school in Talcahuano, Chile, to enhance participation in virtual classes and assignment submissions among third-year high school students. The researcher identified the need to strengthen self-regulated learning competencies, drawing on Barry Zimmerman’s theoretical framework, therefore virtual psychoeducational workshops were developed, and a teacher’s guide was created to promote self-regulated learning. Participation in the workshops was voluntary, and an interactive online platform was used to encourage students’ attendance. The intervention revealed improvements in learning processes, highlighting the workshops’ effectiveness and the teacher’s guide in fostering these competencies. These findings underscore the importance of implementing self-regulated learning strategies, especially in the context of virtual education during the COVID-19 pandemic. The intervention successfully enhanced participation and assignment submission among third-year high school students. Continuation and expansion of similar programs are recommended to enhance learning processes in remote instruction.